An evaluation study of miniature dielectric crossed compound parabolic concentrator (dCCPC) panel as skylights in building energy simulation. (February 2019) - Tian, Meng; Zhang, Li; Su, Yuehong; Xuan, Qingdong; Li, Guiqiang; Lv, Hui
Highlights: Miniature dielectric crossed compound parabolic concentrator (dCCPC) as skylights. The performance of dCCPC skylight panel is compared for fourteen chosen cities. The polynomial transmittance model of dCCPC is implemented in Grasshopper. The energy savings in thermal load and lighting of building are investigated. Abstract: The potential of miniature dielectric crossed compound parabolic concentrator (dCCPC) panel as skylights for daylighting control has drawn a considerable research attention in the recent years, owing to its feature of variable transmittance according to the sun position, but the viability of using it as skylights in buildings has not been explored yet comprehensively. This paper aims to study the feasibility of utilizing miniature dCCPC panel as skylight in different locations under various climates in terms of energy saving potential besides its daylighting control function. The transmittance of dCCPC panel varies at every moment according to the sky condition and sun position. Due to this specific property, this study novelly implemented a polynomial formula of the dCCPC transmittance in the Grasshopper platform, from which EnergyPlus weather data can be called to calculate the hourly transmittance data of dCCPC skylight panel throughout the whole year. An hourly schedule of transmittance is generated according to the hourly sky condition determined by the daylight simulation through Radiance and Daysim, and is then input to EnergyPlus simulation to predict the energy consumption of a building with dCCPC skylight. Fourteen locations around the world are therefore compared to find the most appropriate place for using miniature dCCPC panel as skylights. The energy saving in cooling, heating and lighting with use of dCCPC skylight panel are investigated and compared with low-E and normal double glazing. The results show that the dCCPC skylight panel can reduce cooling load by mitigating solar heat gain effectively although its performance is affected by several criteria such as sky conditions and local climates. It is generally more suitable for the locations with longer hot seasons, e.g., Log Angeles, Miami, Bangkok and Manila, in which dCCPC could provide up to 13% reduction in annual energy consumption of building. For the locations having temperate and continental climates like Beijing, Rome, Istanbul and Hong Kong, a small annual energy saving from 1% to 5% could be obtained by using dCCPC skylight panel.